Responses to language endangerment : in honor of Mickey Noonan : new directions in language documentation and language revitalization - Mihas, Elena; Perley, Bernard C.; Rei Doval, Gabriel; Wheatley, Kathleen; Noonan, Michael (Michael P.) (Studies in language companion series, 2013)
This volume further complicates and advances the contemporary perspective on language endangerment by examining the outcomes of the most commonly cited responses to language endangerment, i.e. language documentation, language revitalization, and training. The present collection takes stock of many complex and pressing issues, such as the assessment of the degree of language endangerment, the contribution of linguistic scholarship to language revitalization programs, the creation of successful language reclamation programs, the emergence of languages that arise as a result of revitalization efforts after interrupted transmission, the ethics of fieldwork, and the training of field linguists and language educators. The volume's case studies provide detailed personal accounts of fieldworkers and language activists who are grappling with issues of language documentation and revitalization in the concrete physical and socio-cultural settings of native speaker communities in different regions of the world.